2009
DOI: 10.1017/s0954579409000042
|View full text |Cite
|
Sign up to set email alerts
|

Stress response and the adolescent transition: Performance versus peer rejection stressors

Abstract: Little is known about normative variation in stress response over the adolescent transition. This study examined neuroendocrine and cardiovascular responses to performance and peer rejection stressors over the adolescent transition in a normative sample. Participants were 82 healthy children (ages 7-12 years, n=39, 22 females) and adolescents (ages 13-17, n=43, 20 females) recruited through community postings. Following a habituation session, participants completed a performance (public speaking, mental arithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
535
8
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(592 citation statements)
references
References 92 publications
46
535
8
3
Order By: Relevance
“…Results confirmed these predictions, where women displayed greater cortisol responses the stressor that elicited 'tending' responses (babies crying), and men displayed greater cortisol responses to threats to the in-group by a clear out-group (protests of military funerals). This is consistent with literature on sex differences in stress responses related to psychosocial stressors in a laboratory setting (Stroud et al 2002(Stroud et al , 2009). Perhaps more importantly, these results also lend empirical support to Geary and Flinn's (2002) predictions that males show greater physiological sensitivity to out-group threat, and females show greater physiological sensitivity to cues related to 'tending.'…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results confirmed these predictions, where women displayed greater cortisol responses the stressor that elicited 'tending' responses (babies crying), and men displayed greater cortisol responses to threats to the in-group by a clear out-group (protests of military funerals). This is consistent with literature on sex differences in stress responses related to psychosocial stressors in a laboratory setting (Stroud et al 2002(Stroud et al , 2009). Perhaps more importantly, these results also lend empirical support to Geary and Flinn's (2002) predictions that males show greater physiological sensitivity to out-group threat, and females show greater physiological sensitivity to cues related to 'tending.'…”
Section: Discussionsupporting
confidence: 92%
“…There is considerable empirical support for using the tend-and-befriend model to predict sex differences in biobehavioral responses to environmental stressors (e.g., Stroud et al 2002Stroud et al , 2009). Related to 'befriending', women appear to use affiliation as a mechanism to reduce stress and appear to be particularly sensitive to gaps in social support networks (Taylor 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research comparing sAA responses in different age groups suggested that children and older adults show attenuated response patterns (Strahler et al, 2010). Studies also suggested that differences in pubertal status might be associated with sAA responses to social evaluative psychological stressors such as the Leiden Public Speaking Task (see van den Bos et al, 2014) or peer rejection (Stroud et al, 2009). Even if the task in the present study did not directly involve social evaluation, it would be interesting for future research to include an objective measure of pubertal status in addition to the assessment of participants' age.…”
Section: Limitations and Further Directionsmentioning
confidence: 98%
“…Although this work has been relevant to some social situations, little work has examined these factors in women's social interactions. Previous research has also shown that females show greater physiological reactivity to social rejection in particular (Stroud et al 2009;Stroud et al 2002). Due to the typical nature of female hierarchies and the value of social support, females' responses to social evaluative threat and, in particular, the role that social positioning plays in females' response have not been thoroughly examined.…”
Section: Current Studymentioning
confidence: 99%
“…Women's hierarchies have been shown to be more unstable than men's (Savin-Williams 1979) and therefore rejection or perceived rejection from a social group may elicit a stress response (especially for women), as it can be a significant threat to the ability to gain social resources (Stroud et al 2009). These social dynamics may have led to sociocognitive mechanisms (i.e., reciprocal altruism) in girls and women that are more attuned to loss of social support and the nuances of same-sex hierarchies (Geary et al 2003).…”
mentioning
confidence: 99%